1983
DOI: 10.1002/ajmg.1320140418
|View full text |Cite
|
Sign up to set email alerts
|

The dup(3)(p25 → pter) syndrome: A case with holoprosencephaly

Abstract: We report a patient with dup(3p) syndrome with holoprosencephaly. This infant is compared with 17 others reported previously with banding studies. In 72% of cases the duplication derived from a mother with a balanced translocation; 78% of affected individuals are males. The most common anomalies are characteristic facial changes, congenital heart defects, and hypoplasia of male genitalia. Holoprosencephaly has not been reported before in the dup(3p) syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0
1

Year Published

1985
1985
2001
2001

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 11 publications
2
16
0
1
Order By: Relevance
“…In case 111-1 of family 2 the severe facial malformation masked the typically milder craniofacial signs. It is of interest that our patient III-1 had holoprosencephaly with cyclopia and that holoprosencephaly was found in the case of Martin and Steinberg (1983). This finding indicates strongly that holoprosencephaly is an uncommon manifestation of the dup(3p) syndrome.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In case 111-1 of family 2 the severe facial malformation masked the typically milder craniofacial signs. It is of interest that our patient III-1 had holoprosencephaly with cyclopia and that holoprosencephaly was found in the case of Martin and Steinberg (1983). This finding indicates strongly that holoprosencephaly is an uncommon manifestation of the dup(3p) syndrome.…”
Section: Discussionsupporting
confidence: 55%
“…How specific is the 3p segment involved? Parloir et a1 [1979], Braga and Schmid [1982], and Martin and Steinberg [1983] seem to favour the hypothesis that the tiny segment 3p25 -+ 3pter is specifically responsible for most of the phenotype of the syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…The spectrum of alobar, semilobar, and lobar holoprosencephaly has been observed in trisomy 13 patients [Colacino and Pettersen, 1978, Gullotta et al, 19821. Holoprosencephaly has been seen in triploidy, dup lq32+qter, dup 3p25-+pter, dup llq21 -+qter, dup 13q22+qter, del 18p and ring 18, and del 13q distal and ring 13; and has been reported in 49 ,XXXXY, trisomy 18, trisomy 21, dup 3q21+pter, dup 6p22+pter, dup 6q21+qter, dup 9p22+pter, dup 14q24+pter, dup 16q, dup 17p, dup 17q23-+qter, dup 22q13+qter, del 4p16.1-+pter, ring 6, del 7q22-rq32, del 7q32-+qter, del lOpl3+pter, ring 15, and del 22qll+pter [Van Regemorter et al, 1981;Hill et al, 1982;Schwartz et al, 1983;Martin and Steinberg, 1983;Roach et al, 1975;Gullotta et al, 1981;Schinzel, 1984a,b].…”
Section: Discussionmentioning
confidence: 96%
“…Buchinger et al (1981) first reported a case of der(18)t(3;18) (p21;p11)mat with microcephaly, bilateral cleft lip and palate, and a flat and retracted nose which looked very much like HPE-PMA. Martin and Steinberg (1983) described a case of cebocephaly with der(4)t(3;4) (p25;q35)mat. Van Regemorter et al (1983) presented a case of HPE-PMA with der(10)t(3;10)(p21;q26)mat.…”
Section: Discussionmentioning
confidence: 98%